Behaviour of RC Beam-Slab Member with Embedded Polystyrene Spheres - Ling, Jen Hua; Lau, Ji Wei; Lim, Yong Tat (Journal of Civil Engineering, 2025)
In this study, four reinforced concrete specimens were produced. Each specimen consisted of two beams and one slab. Polystyrene spheres were used to replace concrete in the beams and slabs in various combinations to reduce weight. The specimens were subjected to an incremental static load under the four-point load setup. The effects of polystyrene spheres on the structural performance of these specimens were investigated. The specimen with solid beams and lightweight slab (i.e., embedded with polystyrene spheres) had the highest material efficiency. Its efficiency was 5% higher than that of the entirely solid specimen. The material's effectiveness decreased by 2% to 4% when the beams were filled with polystyrene spheres. This was regardless of whether the slab contained polystyrene spheres. From feasibility analysis, none of the specimens fulfilled all five assessment criteria. Ductility was a concern for the specimens. The current specimen designs were unable to outstrength the solid specimen. The size and shape of the polystyrene, as well as the dimension of the specimen, may be modified to improve its efficiency.